Complementary vertical sensitivity unlocks full-column thermodynamics from combined ground and space microwave observations - Disong Fu; Qinghui Sun; Fa Tao; Xiangao Xia; Yunjie Xia; Zijue Song; Dazhi Yang; Hongrong Shi; Jiajia Mao; Ziqiang Zhu; Peng Zhang (Atmospheric Research, 2026)

Composite beeswax-glycerol monolaurate oleogelation enhances encapsulation efficiency and oxidative stability of microencapsulated Antarctic krill oil - Xin Sun; Liang Song; Rui-Ying Wang; Xin-Yang Ha; Fa-Wen Yin; Lei Qin; Bei-Wei Zhu; Da-Yong Zhou (Food Research International, 2026)

Iron oxide-apatite and porphyry Cu–Au deposits controlled by pre-ore degassing, emplacement depths, and evaporite assimilation: A comparative study of the Nihe Fe and Shaxi Cu–Au deposits, Anhui, China - Yi Li; Ke-Zhang Qin; Le Wang; Guo-Xue Song; Tao-Fa Zhou; Yong-Jian Wang; Ming-Guo Zhai (Gondwana Research, 2026)

Occurrence, ecological risk, and human health assessment of herbicide residues in Chaohu Lake, China - Yong-mei Zhang; Ping-ping Fan; Ling-zhi Zhang; Wei Yu; Song Xia; Fa-li Liu; Xue-de Li (Journal of Environmental Chemical Engineering, 2026)

A review of strategic enhancement of pollination with smart agriculture to counteract the decline of natural pollinators - Wantong Zhang; Fa Song; Jiyu Sun (Biosystems Engineering, 2026)

Injectable nanocomposite hydrogel with antibacterial/osteogenic dual functions for synergistic repair of infectious bone defects in hyperlipidemia microenvironment - Yongkai Wang; Yunhan Sun; Jiaming Song; Dongchen Fa; Yuting Qu; Jiayi Li; Xiao Fu; Li Ma (Chemical Engineering Journal, 2025)

Different Intensities of Exercise Affect the Prognosis of Ventricular Aneurysm in Mice by Regulating the Progression of Cardiac Fibrosis - Rui-Qiang Qi; Juan Song; Hong-Bin Ma; Mei-Ling Nie; Liu-Hang Su; Cui-Lian Dai; Fa-Guang Zhou; Sui-Ji Li (Cardiovascular Toxicology, 2025)

The application of UAV technology in maize crop protection strategies: A review - Yongwei Yan; Fa Song; Jiyu Sun (Computers and Electronics in Agriculture, 2025)

Furosemide sodium enhanced AQP3 expression by inhibiting NKCC1 leading to improved vitrification freezing rates of mouse and bovine blastocysts - Chang-Guo Min; Xue-Song Shan; Kai-Yan Zhang; Yu-Chan Wang; Xin Ma; Jun Wang; Jing Zhao; Yi Fang; Hong-Yu Liu; He Ding; Dian Wang; Jing Guo; et al. (Theriogenology, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Scalable and fast electrophoresis-accelerated assembly of chiroptical carbon fibers with multi functions - Haixing Jiao; Baiqi Song; Fa Li; Yuanhan Tang; Na Zhang; Xiaofang Zhang; Weilin Xu (Chemical Engineering Journal, 2025)

AdaptiveGS: an explainable genomic selection framework based on adaptive stacking ensemble machine learning - Zhen Yang; Mei Song; Xianggeng Huang; Quanrui Rao; Shanghui Zhang; Zhongzheng Zhang; Chenyang Wang; Wenjia Li; Ran Qin; Chunhua Zhao; Yongzhen Wu; Han Sun; et al. (Theoretical and Applied Genetics, 2025)

Fabrication and application of ferrocene contained MOF derived porous carbon: A single multi-interference clean-up QuEChERS sorbent for facile analysis of triazine herbicides in various fruits and vegetables by LC-MS/MS - Zi-Ling Li; Da-Jin Yang; Jia-Qi Zhao; Wen-Jie Sun; Jie Gao; Shu-Feng Song; Hou-Jun Xu; Hai-Jie Li; Fa-Ming Tian; Man-Man Wang (Food Chemistry, 2025)

Revealing the oxidation mechanism of Antarctic krill oil induced by metal ion: Focusing on the influence of reverse micelles - Xue-Chen Pei; Fa-Wen Yin; Meng-Ling Jin; Xin-Miao Wang; Hui-Lin Liu; Liang Song; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Associations of exposure to arsenic species and endogenous sex hormones with oral cancer: a hospital-based study in Southeastern China - Na Wang; Wenting Zhang; Haoyuan Song; Weihai Huang; Fa Chen; Fengqiong Liu; Yulan Lin; Yu Qiu; Bin Shi; Lisong Lin; Jing Wang; Baochang He (Environmental Pollution, 2025)

Seasonal and regional differences of heavy metals and nutrients from the five mariculture areas of large yellow croaker: Implications for environmental and fish quality - Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Jia-Lang Zheng; Tian-Hong Chen; Shang-Wei Xie; Li-Hua Jiang; Shun Chen; Qing-Ling Zhu; Wei-Hua Song; Xiao-Jun Yan (Environmental Pollution, 2025)

Bioinspired tailless FWMAV design for agricultural plant protection in greenhouses - Yongwei Yan; Fa Song; Wenzhe Wang; Haochen Zhu; Jiyu Sun (Computers and Electronics in Agriculture, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

Exploring eutrophic effects of marine sediments underneath fish cage farms: Insights from changes in eukaryotic and bacterial communities and volatile organic compounds - Fa-Guo Wan; Yong-Long Chen; Jia-Lang Zheng; Wang-Yang Jin; Tian-Hong Chen; Qing-Ling Zhu; Qing-Hao Zhan; Li-Hua Jiang; Shun Chen; Wei-Hua Song; Xiao-Jun Yan (Science of The Total Environment, 2025)

Characterization of a stable QTL for quality-related traits and its effects on yields in wheat (Triticum aestivum L.) - Hongke Ding; Yankun Li; Jinlian Ou; Yuanze Song; Lihua Qiu; Xinyu Rong; Han Sun; Chunhua Zhao; Yongzhen Wu; Ran Qin; Jinlong Li; Cheng Liu; et al. (Theoretical and Applied Genetics, 2025)

Comparison of water quality, planktonic community, and volatile organic compounds in the seawater from five cage culture areas of large yellow croaker - Jia-Lang Zheng; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shang-Wei Xie; Li-Hua Jiang; Shun Chen; Qing-Ling Zhu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2025)

Comparative analysis of carotenoids, fatty acids, minerals, tastes, and odor in the skin of wild versus farmed large yellow croaker: Superior nutritional benefits with elevated heavy metal risks - Jia-Lang Zheng; Tao Zhu; Wang-Yang Jin; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Shuang Chen; Wei-Ye Li; Yi-Fan Liu; et al. (Aquaculture, 2025)

Polyoxometalate oxate solution: An electrolyte additive to sustainably improve the anodes electrode of aqueous Zn ion batteries - Li-li Du; Zhuo Li; Wei-jia Song; Qing-peng Bao; Peng-fei Wang; Zhe Gong; Yu-hang Zhang; Yu-han Wu; Fa-nian Shi; Ming-dong Zhou; Kai Zhu (Chemical Engineering Journal, 2024)

Comparative study on the quality of wild and ecologically farmed large yellow croaker through on-site synchronous sampling from the Nanji Archipelago in the East China Sea - Jia-Lang Zheng; Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Li-Hua Jiang; Wei-Ye Li; Wen-Tao Ye; Yi-Fan Liu; Wei-Hua Song; et al. (Aquaculture, 2024)

The resistance mechanism of humic acids and proteins in soluble microbial products from activated sludge against silver nanoparticles - Jia Kang; Yi-hang Wang; Yao-wen Zhang; Chu-qiong Song; Ao-di Wang; Ning Zhou; Yi-hui Zhang; Fa-zhan Li; Shu-li Liu; Li-sha Liu; Gang-fu Song; Bai-hong Wang (Journal of Environmental Chemical Engineering, 2024)

Unlocking the ultrafast laser response and low initiation energy of perchlorate-free tetrazine-based energetic coordination compounds - Hong-Yi Bian; Yun-Fan Yan; Meng Cui; Hao-Hui Xie; Tian-Tian Song; Xiao-Di Guo; Jian-Gang Xu; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2024)

Sodium Fluoride Exposure Induces Developmental Toxicity and Cardiotoxicity in Zebrafish Embryos - Feiqing Wang; Fa Chen; Wen Song; Yanju Li; Haiyan Wu; Tingting Tian; Mengxian Tian; Dongxin Tang; Yang Liu (Biological Trace Element Research, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Effects of different extraction methods on the structural and biological properties of Hericium coralloides polysaccharides - Zuo-fa Zhang; Guo-ying Lv; Ting-ting Song; Zhou-wei Xu; Meng-yu Wang (Food Chemistry, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Examination of the effects of triacylglycerol lipase on astaxanthin conversion in the black tiger prawn Penaeus monodon - Xin-Tao Li; Li-Shi Yang; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Fa-Lin Zhou; Yun-Dong Li; Jian-Zhi Shi; Xu Chen; Yu-kai Yang; Jian-Hua Huang (Aquaculture, 2024)

Correction to: Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2024)

Investigation on strength behavior of cemented dredged clay with straw at various curing stages - Fa-Hong Wu; Heng Wang; Miao-Miao Song; Cheng-Chun Qiu; Jia-Xing Weng; En-Wei Wang (Marine Georesources & Geotechnology, 2024)

Active/passive protection and anti-UV waterborne epoxy coatings based on low defect functionalized PDA-GO-CeO2 material for excellent corrosion control - Hao Li; Qin-Hao Zhang; Xian-Ze Meng; Hao-Jie Yan; Hui-Song Hu; Lian-Kui Wu; Fa-He Cao (Chemical Engineering Journal, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

One new furanone analogue from the deep-sea fungus Purpureocillium sp. SCSIO 06693 - Ying-Ying Song; Meng-Meng Song; Wei-Hao Chen; Xiao-Yan Pang; Fa-Zuo Wang; Xin-Peng Tian; Jun-Feng Wang; Yong-Hong Liu (Natural Product Research, 2023)

Temperature-dependent NO2/diisopropylamine sensor based on SnO2 squama-wrapped tubes derived from waste bamboo shoot skin - Bao-Yu Song; Cong Chen; Ya-Nan Li; Xian-Fa Zhang; Xiao-Li Cheng; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

Isoquinoline alkaloids from Corydalis edulis Maxim. Exhibiting insulinotropic action - Zhi-Tian Peng; Hui-Xia Huo; Ling-Hui Chao; Yue-Lin Song; Di-Fa Liu; Zhang-Wei Wang; Yuan Zhang; Yun-Fang Zhao; Peng-Fei Tu; Jiao Zheng; Jun Li (Phytochemistry, 2023)

QTL detection for internode diameter and its association with yield-related traits in wheat - Haitao Yu; Yanan Liu; Zongfeng Zou; Xusheng Sun; Jinshan Zhang; Shun Song; Lijie Wang; Ran Qin; Han Sun; Fa Cui; Chunhua Zhao; Shubing Shi (Cereal Research Communications, 2023)

Indole diketopiperazine alkaloids and aromatic polyketides from the Antarctic fungus Penicillium sp. SCSIO 05705 - Yi-Wei Hu; Wei-Hao Chen; Meng-Meng Song; Xiao-Yan Pang; Xin-Peng Tian; Fa-Zuo Wang; Yong-Hong Liu; Jun-Feng Wang (Natural Product Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Review of insect-inspired wing micro air vehicle - Fa Song; Yongwei Yan; Jiyu Sun (Arthropod Structure & Development, 2023)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Effects of soil shrinkage in permanent gullies formation: The case of Benggang erosion in the granite area of southern China - Wan-xia Huang; Yu-song Deng; Chong-fa Cai; Dai-hua Jiang (Journal of Mountain Science, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Crenobacter intestini sp. nov., Isolated from the Intestinal Tract of Konosirus punctatus - Song-Biao Shi; Jia-Fa Wu; Li-Fang Yang; Ming-Guo Jiang; Cai-Mi Gao; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Evaluating the effects of transgenic Bt rice cultivation on soil stability - Ying-ying Song; Jia-wen Liu; Li-kun Li; Man-qiang Liu; Xiao-yun Chen; Fa-jun Chen (Environmental Science and Pollution Research, 2020)

Ottowia flava sp. nov., isolated from fish intestines - Song-Biao Shi; Gui-Ding Li; Li-Fang Yang; Cong Liu; Ming-Guo Jiang; Qin-Yuan Li; Jia-Fa Wu; Kun Zhang; Long-Qian Jiang; Nai-Kun Shen; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Portable vertical pendulum tiltmeter development and application test - Jie-ning Xia; Qiang Lin; Li-Xia Geng; Zhen Li; Song Luo; Nong-Fa Li; Jian-Feng Yu; Jun Liu (Acta Geodaetica et Geophysica, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Identification of QTL regions for seedling root traits and their effect on nitrogen use efficiency in wheat (Triticum aestivum L.) - Xiaoli Fan; Wei Zhang; Na Zhang; Mei Chen; Shusong Zheng; Chunhua Zhao; Jie Han; Jiajia Liu; Xilan Zhang; Liqiang Song; Jun Ji; Xigang Liu; et al. (Theoretical and Applied Genetics, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2018)

Extraction and Characterization of Phospholipid-Enriched Oils from Antarctic Krill ( Euphausia Superba ) with Different Solvents - Fa-Wen Yin; Da-Yong Zhou; Yan-Fei Liu; Qi Zhao; Zhong-Yuan Liu; Liang Song; Xin Zhou; Jian-Run Zhang; Bei-Wei Zhu (Journal of Aquatic Food Product Technology, 2018)

The Forms of Fluoride in Antarctic Krill ( Euphausia superba ) Oil Extracted with Hexane and its Removal with Different Absorbents - Fa-Wen Yin; Da-Yong Zhou; Yan-Fei Liu; Qi Zhao; Xin Zhou; Liang Song; Lei Qin; Hang Qi; Bei-Wei Zhu (Journal of Aquatic Food Product Technology, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Parallel viewshed analysis on a PC cluster system using triple-based irregular partition scheme - Xiao-Dong Song; Guo-An Tang; Xue-Jun Liu; Wan-Feng Dou; Fa-Yuan Li (Earth Science Informatics, 2016)

Identification of a novel frameshift mutation in PITX2 gene in a Chinese family with Axenfeld-Rieger syndrome - Hou-Fa Yin; Xiao-Yun Fang; Chong-Fei Jin; Jin-Fu Yin; Jin-Yu Li; Su-Juan Zhao; Qi Miao; Feng-Wei Song (Journal of Zhejiang University-SCIENCE B, 2014)

Metabolic Changes Detected by Ex Vivo High Resolution 1H NMR Spectroscopy in the Striatum of 6-OHDA-Induced Parkinson’s Rat - Hong-Chang Gao; Huan Zhu; Cai-Yong Song; Li Lin; Yun Xiang; Zhi-Han Yan; Guang-Hui Bai; Fa-Qing Ye; Xiao-Kun Li (Molecular Neurobiology, 2013)

Effects of AM Inoculation and Organic Amendment, Alone or in Combination, on Growth, P Nutrition, and Heavy-Metal Uptake of Tobacco in Pb-Cd-Contaminated Soil - Fa Yuan Wang; Ling Wang; Zhao Yong Shi; You Jun Li; Zhi Mei Song (Journal of Plant Growth Regulation, 2012)

Simulation of biatrial conduction via different pathways during sinus rhythm with a detailed human atrial model - Dong-dong Deng; Ying-lan Gong; Guo-fa Shou; Pei-feng Jiao; Heng-gui Zhang; Xue-song Ye; Ling Xia (Journal of Zhejiang University-SCIENCE B, 2012)

Bt rice expressing Cry1Ab does not stimulate an outbreak of its non-target herbivore, Nilaparvata lugens - Yang Chen; Jun-Ce Tian; Wei Wang; Qi Fang; Zunnu Raen Akhtar; Yu-Fa Peng; Hu Cui; Yu-Yuan Guo; Qi-Sheng Song; Gong-Yin Ye (Transgenic Research, 2012)

Protein sequence analysis based on hydropathy profile of amino acids - Xiao-li Xie; Li-fei Zheng; Ying Yu; Li-ping Liang; Man-cai Guo; John Song; Zhi-fa Yuan (Journal of Zhejiang University-SCIENCE B, 2012)

3D-QSAR and docking studies on pyridopyrazinones as BRAF inhibitors - Yong Ai; Shao-Teng Wang; Chu Tang; Ping-Hua Sun; Fa-Jun Song (Medicinal Chemistry Research, 2011)

A new QTL for resistance to Fusarium ear rot in maize - Zhi-Min Li; Jun-Qiang Ding; Rui-Xia Wang; Jia-Fa Chen; Xiao-Dong Sun; Wei Chen; Wei-Bin Song; Hua-Fang Dong; Xiao-Dong Dai; Zong-Liang Xia; Jian-Yu Wu (Journal of Applied Genetics, 2011)

Dwarf apple MbDREB1 enhances plant tolerance to low temperature, drought, and salt stress via both ABA-dependent and ABA-independent pathways - Wei Yang; Xiao-Dan Liu; Xiao-Juan Chi; Chang-Ai Wu; Yan-Ze Li; Li-Li Song; Xiu-Ming Liu; Yan-Fang Wang; Fa-Wei Wang; Chuang Zhang; Yang Liu; Jun-Mei Zong; et al. (Planta, 2011)

Endemic Seed Plant Species from Hainan Island: A Checklist - Javier Francisco-Ortega; Fa-Guo Wang; Zhong-Sheng Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Seed Plant Endemism on Hainan Island: A Framework for Conservation Actions - Javier Francisco-Ortega; Zhong-Sheng Wang; Fa-Guo Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Analysis of complicated structure seismic wave fields - Hui Zhou; Shang-Xu Wang; Guo-Fa Li; Jin-Song Shen (Applied Geophysics, 2010)

In vitro synergistic activity between 8-methoxypsoralen and ethambutol, isoniazid, and rifampin when used in combination against Mycobacterium tuberculosis - Fa Ge; Fanli Zeng; Na Guo; Junwen Fan; Yu Song; Siguo Liu; Xiuping Wu; Xuelin Wang; Xuming Deng; Qi Jin; Lu Yu (World Journal of Microbiology and Biotechnology, 2010)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.